Usulan Kebijakan Pemeliharan Mesin Untuk Mengurangi Frekuensi Breakdown Menggunakan Reliability Centered Maintenance - Kusnadi, Kusnadi; Wahyudin, Wahyudin; Nugraha, Billy (P3M Politeknik Negeri Cilacap, 2020)
Production process flows are often the obstacles caused by production machine not functioning. Maintenance policies applied today are corrective maintenance and plan maintenance/time direct. Reliability centered maintenance (RCM) it’s method that can be used optimal maintenance action for every part of machine in galvanizing wire system. Steps above method planning consist of a functional block diagram (FBD), system function and function failure (SFFF), failure mode and effect analysis (FMEA), logic tree analysis (LTA), and task selection (TS). The results of analysis RCM method obtained 392 failure mode divided into 83 failure mode which is classified as critical and obtained 59 critical type part. Furthermore, the most appropriate maintenance action for 83 failure critical mode is 55 failure mode in condition directed (CD), 28 failure mode in failure finding (FF) category. Based on design of RCM, this research can reduce the frequency of machine breakdown on galvanizing wire system by 80.98%.